Preparation method of C-coated BiOI composite electrode material and application of C-coated BiOI composite electrode material in aqueous zinc-iodine battery
By using C@BiOI composite electrode material in aqueous zinc-iodine batteries, the problem of slow iodide shuttle and iodine conversion kinetics is solved, and the battery capacity and Coulomb efficiency are improved, suitable for large-scale production and reduced costs.
Patent Information
- Application Number
- CN202510012043.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-06
AI Technical Summary
Water-based zinc-iodine batteries face problems such as multi-iodide shuttle and slow iodine conversion kinetics, which limit their effectiveness in practical applications.
Using C@BiOI composite electrode material, C@BiOI composite electrode material was prepared by dissolving Bi(NO3)2 in a mixed solution of ethanol and ethylene glycol, adding biomass carbon fired from coconut shells, and conducting hydrothermal reactions. Then, the active substance iodine is anchored to the composite material by solution adsorption method, and C@BiOI composite electrode material was prepared.
Effective anchoring of iodine ions improves the specific capacity and rate performance of the material during charging and discharging, improves the energy density and power density of the battery, and reduces production costs, making it suitable for large-scale production.
Smart Images

Figure CN119812275A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of materials, and in particular relates to a preparation method of a C@BiOI composite electrode material and application of the same in an aqueous zinc-iodine battery. Background Art
[0002] The energy crisis has become an imminent problem today. The serious energy problem has prompted people to continuously seek advanced energy storage systems with high economy, environmental friendliness and long cycle life. In energy storage, lithium-ion batteries are widely used in solar and wind power generation systems as a clean energy storage solution with their high energy density and long cycle life. However, despite the excellent performance of lithium-ion batteries in energy density and performance, the limited storage capacity also increases the dependence on scarce resources. Therefore, there is an urgent need to develop safe, reliable and low-cost alternatives to meet the needs of rail transportation and next-generation electronic devices.
[0003] Rechargeable aqueous zinc-ion batteries (RAZBs) are considered to be a new alternative to lithium-ion batteries because of their non-toxic aqueous electrolyte, safety and reliability, and the zinc anode has the advantages of low price, moderate redox potential, and high theoretical capacity. In terms of electrode selection, the conversion reaction of halogen cathodes (Cl, Br, and I) has high theoretical storage capacity and abundant raw materials, while iodine has a high natural abundance (the iodine content in the ocean reaches 55μg L -1 ) has attracted much attention among halogens, which provides a rich source of raw materials for zinc-iodine batteries. Zinc-iodine batteries have gained momentum in various battery systems. They perfectly meet the requirements of industrialization for battery balance and are the most cost-effective batteries among all types of zinc-ion batteries. They not only meet the requirements of performance and stability, but also have excellent prospects to be expected, making them the best choice for the next generation of industrialized battery development. Despite its many advantages, zinc-iodine batteries still face some technical and challenges that limit their large-scale application. Aqueous zinc-iodine batteries face problems such as multi-iodide shuttling and slow iodine conversion kinetics, which limit the effectiveness of zinc-iodine batteries in practical applications. Multi-iodide shuttling will lead to loss of active materials, react with zinc ions at the zinc anode, and produce undesirable self-discharge reactions. In addition, multi-iodides cannot be converted into iodine elemental substance in one step during conversion, and their redox energy storage kinetics are slow. These problems reduce the capacity and coulombic efficiency of the battery. Summary of the invention
[0004] In order to solve the above problems, the present invention provides a method for preparing a C@BiOI composite electrode material and application thereof in an aqueous zinc-iodine battery.
[0005] The technical solution adopted by the present invention is:
[0006] A C@BiOI composite electrode material, the preparation method of which comprises the following steps: 3 ) 2 Dissolved in a mixed solution of ethanol and ethylene glycol, added with biomass carbon burned from coconut shells, stirred at room temperature, hydrothermally reacted, washed, and dried to obtain C@Bi 2 O 3 The composite material is prepared by using a solution adsorption method to anchor the active substance iodine on the composite material to obtain a C@BiOI composite electrode material.
[0007] Furthermore, in the above-mentioned method for preparing a C@BiOI composite electrode material, in the C@BiOI composite electrode material, the molar ratio of C:BiOI=20:1.
[0008] Furthermore, in the above-mentioned method for preparing a C@BiOI composite electrode material, the hydrothermal reaction is carried out in a Teflon-lined high pressure sterilizer at 160° C. for 6 hours.
[0009] Furthermore, in the above-mentioned method for preparing a C@BiOI composite electrode material, the solution adsorption method is to adsorb C@Bi 2 O 3 The composite material was placed in 1 M KI solution and allowed to stand for 6 h.
[0010] Application of a C@BiOI composite electrode material as a positive electrode sheet in an aqueous zinc-iodine battery.
[0011] Further, the above application method is as follows:
[0012] 1) Preparation of negative electrode: A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% was polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm;
[0013] 2) Using the positive electrode sheet coated with the C@BiOI composite electrode material as the positive electrode, using the negative electrode sheet prepared in step 1) as the negative electrode, and the electrolyte being 1M zinc sulfate and 0.1M potassium iodide, to obtain an aqueous zinc-iodine battery.
[0014] Furthermore, in the above application, the method for preparing the positive electrode sheet coated with the C@BiOI composite electrode material comprises the following steps: after the C@BiOI composite electrode material is evenly mixed with the binder and the conductive material, a small amount of NMP is added as a solvent, after mixing evenly, the mixture is directly applied on the substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain the positive electrode sheet coated with the C@BiOI composite electrode material.
[0015] Furthermore, in the above-mentioned method for preparing the positive electrode sheet coated with the C@BiOI composite electrode material, the binder is PVDF.
[0016] Furthermore, in the above-mentioned method for preparing the positive electrode sheet coated with the C@BiOI composite electrode material, the conductive material is Super-p.
[0017] Furthermore, in the method for preparing the positive electrode sheet coated with the C@BiOI composite electrode material, the mass ratio of C@BiOI composite electrode material: binder: conductive material = 8:1:1.
[0018] The beneficial effects of the present invention are:
[0019] 1. By introducing bismuth oxide during the synthesis process, the reaction between bismuth oxide and iodide ions is introduced, which effectively anchors the iodide ions generated during the process.
[0020] 2. Bismuth oxide itself also has redox energy storage properties, which improves the specific capacity and rate performance of the material during the charging and discharging process.
[0021] 3. The electrode material of the present invention has the characteristics of low cost, environmental friendliness and high safety.
[0022] 4. The electrode material of the present invention has the advantages of higher energy density and power density.
[0023] 5. The synthesis process and assembly process of the present invention are simple, easy to operate and control, and suitable for continuous large-scale production.
[0024] 6. After modification, the capacity of the electrode material is increased from 170 mAh g -1 Increased to 340mAh g -1 . BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the XRD spectrum of C@BiOI prepared in Example 1.
[0026] Figure 2 This is the SEM image of C@BiOI prepared in Example 1.
[0027] Figure 3 This is the cyclic voltammetry curve of C@BiOI prepared in Example 1.
[0028] Figure 4 This is the specific capacity diagram of C@BiOI prepared in Example 1. DETAILED DESCRIPTION
[0029] The technical solution of the present invention is further described below, but is not limited thereto. Any modification or equivalent replacement of the technical solution of the present invention without departing from the spirit and scope of the technical solution of the present invention should be included in the protection scope of the present invention.
[0030] Example 1
[0031] (I) The preparation method of C@BiOI is as follows:
[0032] Add 0.97g Bi(NO 3 ) 2 Dissolved in 34 mL of ethanol and 17 mL of ethylene glycol. After stirring at room temperature for 1 hour, 0.48 g of biomass carbon burned from coconut shells was added, and the mixed solution was transferred to a 50 mL Teflon-lined autoclave and stored at 160 ° C for 6 hours. The above product was washed several times with deionized water and ethanol, and dried in a vacuum oven at 80 ° C for 12 hours to obtain C@Bi 2 O 3 Composite material. The C@Bi 2 O 3 The composite material powder was dissolved in 50 mL 1 M KI and allowed to stand for 6 h to allow the active substance iodine to anchor on the composite material to obtain the C@BiOI composite electrode material (ACBI).
[0033] (II) Comparative Example
[0034] Pure biomass carbon (AC): Biomass carbon made from coconut shells was purchased from Kuraray.
[0035] (III) Detection
[0036] Figure 1 is the XRD spectrum of C@BiOI prepared in this example. Figure 1 It can be seen that the XRD spectrum of the sample is basically consistent with the standard spectrum of BiOI, and 27° is the carbon peak. Figure 2 This is the SEM image of C@BiOI. Figure 2 It can be seen that the prepared C@BiOI is a typical flake structure. Figure 3 This is the cyclic voltammetry curve of C@BiOI. Figure 3 It can be seen that the area enclosed by C@BiOI is significantly larger than that of pure biomass carbon, which indicates that the capacity of C@BiOI is greater than that of pure biomass carbon. Figure 4 is the specific capacity diagram of pure biomass carbon and C@BiOI. Figure 4 It can be seen that the specific capacity and cycle stability of C@BiOI are much higher than those of pure biomass carbon.
[0037] Example 2 Preparation of C@BiOI
[0038] Add 0.97g Bi(NO 3 ) 2 Dissolved in 34 mL of ethanol and 17 mL of ethylene glycol. After stirring at room temperature for 1 hour, 0.24 g of biomass carbon burned from coconut shells was added, and the mixed solution was transferred to a 50 mL Teflon-lined autoclave and stored at 160 ° C for 6 hours. The above product was washed several times with deionized water and ethanol, and dried in a vacuum oven at 80 ° C for 12 hours to obtain C@Bi 2 O 3 Composite material. The C@Bi 2 O 3 The composite material powder was dissolved in 50 mL 1 M KI and allowed to stand for 6 h to allow the active substance iodine to anchor on the composite material to obtain the C@BiOI composite electrode material (ACBI).
[0039] Example 3 Preparation of C@BiOI
[0040] Add 0.97g Bi(NO 3 ) 2 Dissolved in 34 mL of ethanol and 17 mL of ethylene glycol. After stirring at room temperature for 1 hour, 0.12 g of biomass carbon made from coconut shells was added, and the mixed solution was transferred to a 50 mL Teflon-lined autoclave and stored at 160 ° C for 6 hours. The above product was washed several times with deionized water and ethanol, and dried in a vacuum oven at 80 ° C for 12 hours to obtain C@Bi 2 O 3 Composite material. The C@Bi 2 O 3 The composite material powder was dissolved in 50 mL 1 M KI and allowed to stand for 6 h to allow the active substance iodine to anchor on the composite material to obtain the C@BiOI composite electrode material (ACBI).
[0041] Example 4 Preparation of C@BiOI
[0042] Add 0.97g Bi(NO 3 ) 2 Dissolved in 34 mL of ethanol and 17 mL of ethylene glycol. After stirring at room temperature for 1 hour, 0.96 g of biomass carbon burned from coconut shells was added, and the mixed solution was transferred to a 50 mL Teflon-lined autoclave and stored at 160 ° C for 6 hours. The above product was washed several times with deionized water and ethanol, and dried in a vacuum oven at 80 ° C for 12 hours to obtain C@Bi 2 O 3 Composite material. The C@Bi 2 O 3The composite material powder was dissolved in 50 mL 1 M KI and allowed to stand for 6 h to allow the active substance iodine to anchor on the composite material to obtain the C@BiOI composite electrode material (ACBI).
[0043] Example 5 Preparation of negative electrode material
[0044] A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% was repeatedly polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm for later use.
[0045] Example 6 Preparation of aqueous zinc-iodine battery
[0046] 1) Preparation of positive electrode: After the C@BiOI composite electrode material prepared in Example 1 is uniformly mixed with PVDF and Super-p (by mass ratio, 8:1:1), a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain a positive electrode sheet coated with the C@BiOI composite electrode material;
[0047] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 1 M zinc sulfate and 0.1 M potassium iodide were selected as the electrolyte to obtain an aqueous zinc-iodine battery and perform electrochemical testing.
[0048] Example 7 Preparation of aqueous zinc-iodine battery
[0049] 1) Preparation of positive electrode: After the C@BiOI composite electrode material prepared in Example 2 is uniformly mixed with PVDF and Super-p (by mass ratio, 8:1:1), a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain a positive electrode sheet coated with the C@BiOI composite electrode material;
[0050] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 1 M zinc sulfate and 0.1 M potassium iodide were selected as the electrolyte to obtain an aqueous zinc-iodine battery and perform electrochemical testing.
[0051] Example 8 Preparation of aqueous zinc-iodine battery
[0052] 1) Preparation of positive electrode: After the C@BiOI composite electrode material prepared in Example 3 is uniformly mixed with PVDF and Super-p (by mass ratio, 8:1:1), a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain a positive electrode sheet coated with the C@BiOI composite electrode material;
[0053] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 1 M zinc sulfate and 0.1 M potassium iodide were selected as the electrolyte to obtain an aqueous zinc-iodine battery and perform electrochemical testing.
[0054] Example 9 Preparation of aqueous zinc-iodine battery
[0055] 1) Preparation of positive electrode: After the C@BiOI composite electrode material prepared in Example 4 is uniformly mixed with PVDF and Super-p (by mass ratio, 8:1:1), a small amount of NMP is added as a solvent, and after uniform mixing, it is directly applied on the substrate carbon paper, placed in a vacuum drying oven for drying, and then taken out to obtain a positive electrode sheet coated with the C@BiOI composite electrode material;
[0056] 2) The positive electrode sheet prepared in step 1) was used as the positive electrode, the negative electrode sheet prepared in Example 5 was used as the negative electrode, and 1 M zinc sulfate and 0.1 M potassium iodide were selected as the electrolyte to obtain an aqueous zinc-iodine battery and perform electrochemical testing.
[0057] According to the four aqueous zinc-iodine ion batteries assembled according to the above Examples 6 to 9, we obtained that Example 6 had the best electrochemical performance, and at a current density of 3Ag -1 The long cycle life reaches 1000 cycles, and the capacity retention rate is 86.39% (such as Figure 4 As shown, in the C@BiOI material formed when C:BiOI=20:1 in Example 6, BiOI is deposited on carbon more uniformly and orderly, and more and more uniform iodine ion adsorption sites are obtained on carbon, which has a more favorable effect on the separation of iodine element and iodide ions, thereby improving its electrochemical performance.
Claims
1. A C@BiOI composite electrode material, characterized in that: The preparation method comprises the following steps: dissolving Bi(NO3)2 in a mixed solution of ethanol and ethylene glycol, adding biomass carbon fired from coconut shells, stirring at room temperature, performing hydrothermal reaction, washing, and drying to obtain a C@Bi2O3 composite material; and anchoring the active substance iodine on the composite material through a solution adsorption method to obtain a C@BiOI composite electrode material.
2. A C@BiOI composite electrode material according to claim 1, characterized in that: In the C@BiOI composite electrode material, in molar ratio, C:BiOI=20:
1.
3. The C@BiOI composite electrode material according to claim 1, characterized in that: The hydrothermal reaction was carried out in a Teflon-lined autoclave at 160° C. for 6 h.
4. The C@BiOI composite electrode material according to claim 1, characterized in that: The solution adsorption method is to place the C@Bi2O3 composite material in a 1M KI solution at room temperature and let it stand for 6 hours.
5. Use of a C@BiOI composite electrode material as claimed in any one of claims 1 to 4 as a positive electrode sheet in an aqueous zinc-iodine battery.
6. The use according to claim 5, characterized in that: Here’s how: 1) Preparation of negative electrode: A zinc sheet with a thickness of 0.1 mm and a purity of 99.99% was polished with sandpaper to remove the oxide layer on the surface, and the polished zinc sheet was cut into a circular negative electrode sheet with a diameter of 12 mm; 2) Using the positive electrode sheet coated with the C@BiOI composite electrode material as the positive electrode, using the negative electrode sheet prepared in step 1) as the negative electrode, and the electrolyte being 1M zinc sulfate and 0.1M potassium iodide, to obtain an aqueous zinc-iodine battery.
7. The use according to claim 6, characterized in that: The preparation method of the positive electrode sheet coated with the C@BiOI composite electrode material comprises the following steps: after the C@BiOI composite electrode material is uniformly mixed with a binder and a conductive material, a small amount of NMP is added as a solvent, after uniform mixing, the mixture is directly applied on a substrate carbon paper, dried in a vacuum drying oven, and taken out to obtain a positive electrode sheet coated with the C@BiOI composite electrode material.
8. The use according to claim 7, characterized in that: The binder is PVDF.
9. The use according to claim 7, characterized in that: The conductive material is Super-p.
10. The use according to claim 7, characterized in that: In terms of mass ratio, C@BiOI composite electrode material: binder: conductive material = 8:1:1.
Citation Information
Patent Citations
Preparation method of laminar pearl bismuth oxychloride
CN103130275A
Bismuth oxyhalide aqueous zinc ion secondary battery positive electrode and preparation method and application thereof
CN110416531A
Preparation method of hollow tubular ceiba floc biomass carbon composite material
CN117019182A
Brine-based dual-ion battery system and application thereof
CN117673502A
Bismuth oxyhalide-based quantum dots and method of synthesis thereof
US12110434B1